Standardisation of smart cities - an Indian perspective. (3rd June 2019) - Majumdar, Pradeep; Das, Bhagwan; Garg, Shivani
Idea of smart cities in developing world like India is still in concept developing mode. There is literature available dealing with the preface activity to the smart city development, in the developed world. With this background in the present paper, questionnaire surveys were carried out in a city, selected to be developed as smart city by the Indian Government. Based upon survey data, rankings were setup for the parameters suggested by British Survey Institute. The outcome is compared with the opinions developed in past surveys, carried out in developed countries. The survey shows, except communication, there are wide variations in the rankings of various ingredients between developing and the developed world. Do the information and communications remain significant irrespective of the socio-economic variations? From what kind of base line, a smart city should be developed? What could be the pathway for developing a smart city in developing world? The present paper discusses and recommends these related issues regarding smart city development in India.